Matrilineal analysis of mutations in the DMD gene in a multigenerational South Indian cohort using DMD gene panel sequencing. Issue 5 (7th May 2021) - Shastry, Arun; Aravind, Sankaramoorthy; Sunil, Meeta; Ramesh, Keerthi; Ashley, Berty; T., Nithyanandan; Ramprasad, Vedam L.; Gupta, Ravi; Seshagiri, Somasekar; Nongthomba, Upendra; Phalke, Sameer
Abstract: Background: Duchenne muscular dystrophy (DMD) is an X‐linked recessive neuromuscular disorder characterised by progressive irreversible muscle weakness, primarily of the skeletal and the cardiac muscles. DMD is characterised by mutations in the dystrophin gene, resulting in the absence or sparse quantities of dystrophin protein. A precise and timely molecular detection of DMD mutations encourages interventions such as carrier genetic counselling and in undertaking therapeutic measures for the DMD patients. Results: In this study, we developed a 2.1 Mb custom DMD gene panel that spans the entire DMD gene, including the exons and introns. The panel also includes the probes against 80 additional genes known to be mutated in other muscular dystrophies. This custom DMD gene panel was used to identify single nucleotide variants (SNVs) and large deletions with precise breakpoints in 77 samples that included 24 DMD patients and their matrilineage across four generations. We used this panel to evaluate the inheritance pattern of DMD mutations in maternal subjects representing 24 DMD patients. Conclusion: Here we report our observations on the inheritance pattern of DMD gene mutations in matrilineage samples across four generations. Additionally, our data suggest that the DMD gene panel designed by us can be routinely used as a single genetic test to identify all DMD gene variants in DMD patients and the carrier mothers. Abstract : In this study we have used an Next Generation Sequencing (NGS) panel covering the whole DMD gene to identify mutations in the 24 DMD patients and their matriliniage for up to four generations.